Biotechnological Approaches on Two High CBD and CBG Cannabis sativa L. (Cannabaceae) Varieties: In Vitro Regeneration and Phytochemical Consistency Evaluation of Micropropagated Plants Using Quantitative 1H-NMR - Kostas Ioannidis (Molecules, 2020)
High cannabidiol (CBD) and cannabigerol (CBG) varieties of Cannabis sativa L., a species with medicinal properties, were regenerated in vitro. Explants of nodal segments including healthy axillary bud, after sterilization, were placed in Murashige-Skoog (MS) culture medium. The shoots formed after 30 days were subcultured in full- or half-strength MS medium supplemented with several concentrations of 6-benzyl-amino-purine (BA) or thidiazuron (TDZ). The highest average number and length of shoots was achieved when both full and half-strength MS media were supplemented with 4.0 μM BA. The presence of 4.0 μM TDZ showed also comparable results. BA and TDZ at concentrations of 4.0, 8.0 μM and 2.0, 4.0 μM respectively, displayed the maximum shooting frequency. The new shoots were transferred on the same media and were either self-rooted or after being enhanced with different concentrations of indole-3-butyric acid (IBA) or α-naphthalene acetic acid (NAA). Presence of 2.0 or 4.0 μM IBA or 4.0 μM NAA resulted to the optimum rooting rates. The maximum average number and length of roots per shoot was observed when the culture media was supplemented with 4.0 μM IBA or NAA. Approximately 92% of the plantlets were successfully established and acclimatized in field. The consistency of the chemical profile of the acclimatized in vitro propagated clones was assessed using quantitative 1H-NMR high throughput screening. In each variety, analysis of the micropropagated plant in comparison with the mother plant showed no statistically significant differences (p ≤ 0.05) in CBD+ cannabidiolic acid (CBDA) and CBG+ cannabigerolic acid (CBGA) content respectively, thus indicating stability of their chemical profile.